2014
DOI: 10.2308/ajpt-50793
|View full text |Cite
|
Sign up to set email alerts
|

Do Critical Audit Matter Paragraphs in the Audit Report Change Nonprofessional Investors' Decision to Invest?

Abstract: SUMMARY: Both U.S. and international standard setters have recently proposed changes to the standard audit report, including a requirement to include a critical audit matter (CAM) paragraph. We examine how nonprofessional investors react to an audit report's CAM paragraph that is centered on the audit of fair value estimates. We perform an experiment with nonprofessional investors who are business school graduates who invest in individual stocks and analyze company financial data. We find that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
211
0
16

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(239 citation statements)
references
References 24 publications
12
211
0
16
Order By: Relevance
“…Likewise, the adoption of ISA is also associated with ARQ in line with prior studies such as Boolaky () and Christensen et al. (). The authors suggest that investors are more reliant on the audit report if the latter provides information on key audit matters as required by the revised ISA on audit reporting.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Likewise, the adoption of ISA is also associated with ARQ in line with prior studies such as Boolaky () and Christensen et al. (). The authors suggest that investors are more reliant on the audit report if the latter provides information on key audit matters as required by the revised ISA on audit reporting.…”
supporting
confidence: 87%
“…Lastly, following the approval of a revised standard for a new reporting model by the IAASB in 2014, Christensen et al. () conducted an experimental study to examine how nonprofessional investors react to a key audit matter (KAM) paragraph in the new audit reporting model. The experiment was performed on a number of business school graduates (nonprofessional investors) who invested in stocks and analysed company financial data.…”
Section: Arq: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this archival study from France, there are some North American experimental studies on the effect of KAM disclosure (or critical audit matters, the term used by the PCAOB). Christensen, Glover and Wolfe () performed an experiment with nonprofessional investors who are business school alumni of a large, public US university who invest in individual stocks and analyse company financial data. They investigated how these subjects react to an audit report's critical audit matter paragraph that is centred on the audit of fair value estimates, and found that investors are indeed more likely to stop considering the firm as an investment.…”
Section: Prior Research and Research Questionsmentioning
confidence: 99%
“…For research concerning KAM, see Christensen, Glover, and Wolfe (), Simnett and Huggins (), Kachelmeier, Schmidt, and Valentine (), Sirois, Bédard, and Bera (), Brasel et al (), Boolaky and Quick () and Gimbar, Hansen, and Ozlanski ().…”
mentioning
confidence: 99%